2001
DOI: 10.1021/ac010542e
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical and Quartz Crystal Microbalance Detection of the Cholera Toxin Employing Horseradish Peroxidase And GM1-Functionalized Liposomes

Abstract: An ultrasensitive method for the detection of the cholera toxin (CT) using electrochemical or microgravimetric quartz crystal microbalance transduction means is described. Horseradish peroxidase (HRP) and GM1-functionalized liposomes act as catalytic recognition labels for the amplified detection of the cholera toxin based on highly specific recognition of CT by the ganglioside GM1. The sensing interface consists of monoclonal antibody against the B subunit of CT that is linked to protein G, assembled as a mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
132
0
10

Year Published

2003
2003
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 177 publications
(145 citation statements)
references
References 40 publications
3
132
0
10
Order By: Relevance
“…Recently, Cremona et al (55) have shown that localization of the transporter in the cholesterol-rich membrane raft microdomains is essential for the AMPH-induced reversed transport of dopamine in dopaminergic neurons. GM1 (monosialotetrahexosylganglioside) is a well characterized membrane ganglioside that is distributed in the cholesterol-enriched membrane microdomains (56) and has been show to interact with and recruit ␣-synuclein to membrane rafts (57). We used confocal microscopy to examine the hypothesis that elevated ␣-synuclein affects the membrane microdomain distribution of DAT to regulate its activity.…”
Section: Dopamine Transporter and ␣-Synucleinmentioning
confidence: 99%
“…Recently, Cremona et al (55) have shown that localization of the transporter in the cholesterol-rich membrane raft microdomains is essential for the AMPH-induced reversed transport of dopamine in dopaminergic neurons. GM1 (monosialotetrahexosylganglioside) is a well characterized membrane ganglioside that is distributed in the cholesterol-enriched membrane microdomains (56) and has been show to interact with and recruit ␣-synuclein to membrane rafts (57). We used confocal microscopy to examine the hypothesis that elevated ␣-synuclein affects the membrane microdomain distribution of DAT to regulate its activity.…”
Section: Dopamine Transporter and ␣-Synucleinmentioning
confidence: 99%
“…Thus, the flow system arrangement coupled with ac adsorptive stripping voltammetry was used to demonstrate detection of pneumolysin and interkeulin at picogram per milliliter levels by employing a conventional ELISA approach with alkaline phosphatase label [16]. Willner's group reported on the use of chronopotentiometry and Faradic impedance spectroscopy for the transduction of an amplified immunosensing scheme that consisted of the biocatalytic precipitation of an insoluble product onto a gold electrode surface [17][18][19]. Hwang et al developed a DNA sensor that used stripping voltammetry to detect the accumulated silver metal reduced by enzyme-generated product [20].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, classic CT determinations require the use of either animal methods (5,6) or tissue culture methods (7,8), which are also time-consuming and are subjective in the interpretation of results. Efforts have been made recently to develop more-sensitive methods, including enzyme-linked immunosorbent assays (9), latex agglutination assays (10), coagglutination assays (5), liposome-based assays (9,11), radioimmunoassays (12), hydrogel-based immunoassays (13), monosaccharide-and antibody array-based assays (14)(15)(16)(17), PCR-based molecular assays (10,(18)(19)(20)(21), and biosensor-based assays (22)(23)(24)(25)(26)(27)(28)(29)(30)(31). A reliable laboratory tool is desirable for clinical services and epidemiological investigation, to characterize CT activities rapidly and quantitatively.…”
mentioning
confidence: 99%